Application of CRISPR/Cas9 in Understanding Avian Viruses and Developing Poultry Vaccines - Vilela, Julianne; Rohaim, Mohammed A.; Munir, Muhammad (Frontiers in Cellular and Infection Microbiology, 2020)
The clustered regularly interspaced short palindromic repeats (CRISPR)-associated protein nuclease 9 (Cas9) system is a novel approach that is attributed by a precise, cost-effective and easy-to-use gene editing platform for a wide array of applications across multiple discipline. The CRISPR/Cas9 technology provides tools to underpin fundamentals of host-virus interactions, elucidate viral gene functions, and development recombinant vaccines. The successful utilization of CRISPR/Cas9 in editing viral genomes can pave the way of developing novel and recombinant viral vectored poultry vaccines. Furthermore, CRISPR/Cas9 can be exploited to rectify major limitations in the development of viral vectored vaccines by convectional approaches including reversion to virulent form, recombination with field viruses and transgene, and genome instability. This review provides comprehensive analysis of the potential of CRISPR/Cas9 genome editing technique in understanding avian virus-host interactions and developing novel poultry vaccines. Finally, we discuss simplest and practical aspects of genome editing approaches in generating multivalent recombinant poultry vaccines that conform simultaneous protection against major avian diseases.